2018
DOI: 10.1177/1533317518768999
|View full text |Cite
|
Sign up to set email alerts
|

Use of Potentially Inappropriate Medications in People With Dementia in Vietnam and Its Associated Factors

Abstract: This study examined the use of potentially inappropriate medicines that may affect cognition (PIMcog) in people with dementia and its associated factors. Medical records of all outpatients with dementia attending a tertiary hospital in Vietnam between January 1, 2015, and December 31, 2016, were examined. Medicine use was assessed against a list of PIMcog. Variables associated with having a PIMcog were assessed using a multiple logistic regression. Of the 128 patients, 41% used a PIMcog, 39.1% used cholinester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…After removing duplication (n = 1,302), 4,337 records were used to screen the title and abstract. Finally, 62 studies (Zuckerman et al, 2005;Raivio et al, 2006;Holmes et al, 2008;Chan et al, 2009;Lau et al, 2010;Somers et al, 2010;Tjia et al, 2010;Andersen et al, 2011;Lau et al, 2011;Bosboom et al, 2012;Colloca et al, 2012;Parsons et al, 2012;Thorpe et al, 2012;Fiss et al, 2013;Koyama et al, 2013;Montastruc et al, 2013;Toscani et al, 2013;Tjia et al, 2014;Hanlon et al, 2015;Skoldunger et al, 2015;Barry et al, 2016;Cross et al, 2016;Walsh et al, 2016;Chuang et al, 2017;Clague et al, 2017;Hyttinen et al, 2017;Kanagaratnam et al, 2017;Oesterhus et al, 2017;Ramsey et al, 2017;Wucherer et al, 2017;Kristensen et al, 2018;Nguyen et al, 2018;Renom-Guiteras et al, 2018;Bala et al, 2019;Brimelow et al, 2019;Denholm et al, 2019;Eshetie et al, 2019a;Kristensen et al, 2019;Soysal et al, 2019;Eshetie et al, 2020;Eshetie et al...…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…After removing duplication (n = 1,302), 4,337 records were used to screen the title and abstract. Finally, 62 studies (Zuckerman et al, 2005;Raivio et al, 2006;Holmes et al, 2008;Chan et al, 2009;Lau et al, 2010;Somers et al, 2010;Tjia et al, 2010;Andersen et al, 2011;Lau et al, 2011;Bosboom et al, 2012;Colloca et al, 2012;Parsons et al, 2012;Thorpe et al, 2012;Fiss et al, 2013;Koyama et al, 2013;Montastruc et al, 2013;Toscani et al, 2013;Tjia et al, 2014;Hanlon et al, 2015;Skoldunger et al, 2015;Barry et al, 2016;Cross et al, 2016;Walsh et al, 2016;Chuang et al, 2017;Clague et al, 2017;Hyttinen et al, 2017;Kanagaratnam et al, 2017;Oesterhus et al, 2017;Ramsey et al, 2017;Wucherer et al, 2017;Kristensen et al, 2018;Nguyen et al, 2018;Renom-Guiteras et al, 2018;Bala et al, 2019;Brimelow et al, 2019;Denholm et al, 2019;Eshetie et al, 2019a;Kristensen et al, 2019;Soysal et al, 2019;Eshetie et al, 2020;Eshetie et al...…”
Section: Study Selectionmentioning
confidence: 99%
“…Of all included studies, 53 studies reported the prevalence of PIM (Zuckerman et al, 2005;Raivio et al, 2006;Holmes et al, 2008; Frontiers in Pharmacology frontiersin.org Frontiers in Pharmacology frontiersin.org conducted in South America (Forgerini et al, 2020;Ferreira et al, 2021), and the rest of the studies conducted in Oceania (Somers et al, 2010;Bosboom et al, 2012;Cross et al, 2016;Bala et al, 2019;Eshetie et al, 2019b;Brimelow et al, 2019;Eshetie et al, 2020;Eshetie et al, 2020;Ruangritchankul et al, 2020;Thapaliya et al, 2021) (n = 10), North America (Zuckerman et al, 2005;Holmes et al, 2008;Chan et al, 2009;Lau et al, 2010;Tjia et al, 2010;Lau et al, 2011;Thorpe et al, 2012;Koyama et al, 2013;Tjia et al, 2014;Hanlon et al, 2015;Ramsey et al, 2017;Growdon et al, 2021;Vickers et al, 2021;Bae-Shaaw et al, 2023;Ryskina et al, 2023) (n = 15), and Asia (Chuang et al, 2017;Nguyen et al, 2018;Chao et al, 2022;Yoon et al, 2022;Zhao et al, 2022) (n = 5). Table 1 presents the characteristics of the included studies.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of cognitive symptoms of dementia in adults aged 60 years and above is relatively high in Vietnam (14.4-46.4%) 23,24 with an estimated 2.4 million people living with dementia in Vietnam by 2050. 25 Advancing the mental health of older people in Vietnam is critical in the face of population growth and increased living standards resulting in longer lifespan. In the first Vietnam National Dementia Conference, dementia was recognized as a public health priority in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 60% of people with dementia live in low- and middle-income countries (LMICs) and the costs of care are mostly borne by family members [ 2 ]. Health and social care systems in LMICs are often not well-developed or well-funded, resulting in unmet care needs for people with dementia and their carers [ 3 , 4 ]. In high-income countries (HICs), most people with dementia also live at home and receive care from their families [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%